RANCANGAN APLIKASI INDEKS KINERJA DOSEN PADA STAFFSITE STMIK PPKIA PRADNYA PARAMITA MALANG - Widarti, Dinny Wahyu; Firdaus, Nasrul (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2018)
The IKAD Information System application at STIMATA is still done in the conventional way. Collecting Tridharma data for each lecturer such as teaching, research and dedication as well as questionnaire data from students, then entering data and entering the IKAD formula. So far, the calculation of IKAD uses Microsoft Excel. Then the secretary of the study program made a letter of IKAD by combining the calculation data of IKAD. Then the letter was distributed to the Lecturers through BAAK. Letters distributed to lecturers often settle for days in the BAAK room. The delay in the process of making IKAD makes each lecturer slow for self-introspection, so that in the next semester there has been no better progress.On the basis of the above problems, it is necessary to make the IKAD Application in Web-based STIMATA. This research was carried out with the SDLC method. The IKAD application will be placed on the staffsite.stimata.ac.id page.It is expected that by using the IKAD application it can reduce the entry processing time and ease of data calculation, and can produce lecturer report cards quickly, as well as graphical display of lecturers' achievement every semester